Effectiveness, Of Effectiveness Of Computer Utilization At The Makassar State Administrative Court Office: Effectiveness Of Computer Utilization At The Makassar State Administrative Court Office - Nasrullah, Muh.; Zarni Adia Purna; Nasir, Nasir; Darmawan, Rahmat (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2024)
Effectiveness is the main element in achieving a predetermined goal or goal. Effectiveness is the achievement of various goals that have been determined on time by using certain resources that have been allocated to carry out various activities. A job can be said to be effective if the results achieved are in accordance with the goals that have been set pre-determined and on time that has been determined. In simple terms, work effectiveness can be defined as the ability to do something right on target. As one of the public service offices, it will serve various kinds of transactions in their daily lives in providing protection for people's rights and legal certainty both for the people and for state administration as well as a means to resolve conflicts that arise between the government and the people. The State Administrative Court is tasked and has the authority to examine, decide, and resolve State Administrative disputes. As one of the public service offices, of course, the effectiveness and efficiency of services are very important, the greater the service services in the office, the more complex the types of actions and services that must be provided, all of which must remain in an integrated coordination.